Nuclear calcium signaling in D1 receptor-expressing neurons of the nucleus accumbens regulates molecular, cellular, and behavioral adaptations to cocaine - Saint-Jour, Estefani; Allichon, Marie-Charlotte; Andrianarivelo, Andry; Montalban, Enrica; Martin, Claire; Huet, Lisa; Heck, Nicolas; Hertle, Anna M.; Ravenhorst, Aisha; Marias, Mélanie; Gervasi, Nicolas; Arrivet, Faustine; et al. (Biological psychiatry, 2025)
Background - The persistence of cocaine-evoked adaptations relies on gene regulations within the reward circuit, especially in the ventral striatum (i.e., nucleus accumbens [NAc]). Notably, activation of the ERK (extracellular signal-regulated kinase) pathway in the striatum is known to trigger a transcriptional program shaping long-term responses to cocaine. Nuclear calcium signaling has also been shown to control multiple forms of transcription-dependent neuroadaptations, but the dynamics and roles of striatal nuclear calcium signaling in preclinical models of addiction remain unknown. - Methods - A genetically encoded cell type-specific nuclear calcium probe has been developed to monitor calcium dynamics in the nuclei of striatal neurons, including in freely moving mice. A cell type-specific inhibitor of nuclear calcium signaling combined with 3-dimensional imaging of neuronal morphology, immunostaining, and behavior was used to disentangle the roles of nuclear calcium in NAc medium spiny neurons (MSNs) expressing the dopamine D1 receptor (D1R) or D2 receptor (D2R) on cocaine-evoked responses. - Results - The D1R-mediated potentiation of calcium influx through glutamate NMDA receptors, which shapes cocaine effects, also drives nuclear calcium transients. Fiber photometry revealed that cocaine-treated mice showed a sustained nuclear calcium increase in NAc D1R-MSNs. Disrupting nuclear calcium in D1R-MSNs, but not D2R-MSNs, blocked cocaine-evoked morphological changes of MSNs and gene expression and blunted cocaine’s rewarding effects. - Conclusions - Our study unravels the dynamics and roles of cocaine-induced nuclear calcium signaling increases in D1R-MSNs on molecular, cellular, and behavioral adaptations to cocaine and represents a significant breakthrough because it could contribute to the development of innovative strategies with therapeutic potential to alleviate addiction symptoms.